Feasibility of Leadless Cardiac Pacing Using Injectable Magnetic Microparticles - Rotenberg, Menahem Y. (Sci Rep, 2016)
A noninvasive, effective approach for immediate and painless heart pacing would have invaluable implications in several clinical scenarios. Here we present a novel strategy that utilizes the well-known mechano-electric feedback of the heart to evoke cardiac pacing, while relying on magnetic microparticles as leadless mechanical stimulators. We demonstrate that after localizing intravenously-injected magnetic microparticles in the right ventricular cavity using an external electromagnet, the application of magnetic pulses generates mechanical stimulation that provokes ventricular overdrive pacing in the rat heart. This temporary pacing consistently managed to revert drug-induced bradycardia, but could only last up to several seconds in the rat model, most likely due to escape of the particles between the applied pulses using our current experimental setting. In a pig model with open chest, MEF-based pacing was induced by banging magnetic particles and has lasted for a longer time. Due to overheating of the electromagnet, we intentionally terminated the experiments after 2 min. Our results demonstrate for the first time the feasibility of external leadless temporary pacing, using injectable magnetic microparticles that are manipulated by an external electromagnet. This new approach can have important utilities in clinical settings in which immediate and painless control of cardiac rhythm is required.